Problematika Implementasi Kurikulum 2013 Dalam Pembelajaran Bahasa Arab di Pondok Pesantren MA Bahrul Ulum Muliasari-Banyuasin - Jamanuddin, Jamanuddin; Ibrahim, Ibrahim (El-Idare, 2021)
This article is titled Problematika Implementation curriculum 2013 In Arabic Learning in Pondok Pesantren MA Bahrul Ulum Muliasari, against the background of the problem that in the process of learning Arabic teachers still have many problems, both administratively and also in the implementation in the field. The must-implement curriculum 2013 (K13) has been regulated by the government, schools / madrassas are obliged in carrying it out. The results of this study are problematic implementation of K13 in Arabic learning starting from planning namely the preparation of RPP i.e. teachers do not yet understand in drafting learning, making assessments and other activities on learning planning. At the time of learning, the initial activities were already well underway, but in the core activities, teachers often had difficulty in their implementation, as many students did not have much memorization of vocabulary or mufrodat. In the last stage of closing, teachers often do not reflect on the lessons learned before. While the causative factor of the emergence of problematic is the ability of teachers in making arabic learning programs and evaluations into scientific approaches, Teachers do not make RPP as a guideline in teaching, when teachers do not make RPP as a guideline in teaching of course learning will take place undirected, this is seen by the many steps in learning that teachers do not implement. From the above problems teachers should learn more related to the flow or learning process created by the Government in the 2013 curriculum. From the assessment aspect of the teacher has not understood how to do a good penialain in accordance with K13, then the teacher should be able to see the guidelines that have been made by the government related to the assessment.